2014
DOI: 10.1155/2014/129697
|View full text |Cite
|
Sign up to set email alerts
|

Achyranthes asperaRoot Extracts Induce Human Colon Cancer Cell (COLO-205) Death by Triggering the Mitochondrial Apoptosis Pathway and S Phase Cell Cycle Arrest

Abstract: Achyranthes aspera (AA) has been used traditionally for the cure of various disorders. However, the action of root extracts of AA as anticancer agent and its cellular mechanism remain unclear. The aim was to screen the antitumor effect of ethanolic (EAA) and aqueous (AAA) root extracts on the growth of colon cancer COLO-205 cells by testing their cytotoxicity, followed by their effect on clonogenicity, migration, and induction of apoptosis. Mechanisms leading to apoptosis and cell cycle arrest were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Bufalin was shown to be potent against human OS tissues and cell lines via inducing apoptosis (20,21); however, the specific underlying mechanism has remained elusive. Mitochondria-mediated signaling pathways have a pivotal role in the process of apoptosis (22)(23)(24)(25), and have been identified to be the underlying mechanism of bufalin-induced apoptosis in various types of tumor cell (21). As the specific mechanisms of action of bufalin vary between different tumor types or even between different phenotypes of the same tumor type, the mechanisms of the effects of bufalin on OS cell lines require to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Bufalin was shown to be potent against human OS tissues and cell lines via inducing apoptosis (20,21); however, the specific underlying mechanism has remained elusive. Mitochondria-mediated signaling pathways have a pivotal role in the process of apoptosis (22)(23)(24)(25), and have been identified to be the underlying mechanism of bufalin-induced apoptosis in various types of tumor cell (21). As the specific mechanisms of action of bufalin vary between different tumor types or even between different phenotypes of the same tumor type, the mechanisms of the effects of bufalin on OS cell lines require to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For a cell to be able to divide into two daughter cells, the synthesis and duplication of the DNA are a requirement, and any abnormality in this would lead to an obstacle in cell cycle progression. Numerous checkpoints exist to aid cells in the identification and repair of DNA damage by halting/stalling the progression through the phases of the cell cycle, including the G 0 /G 1 , S and G 2 /M checkpoints (40). The current study observed arrest at the S to G 2 /M phase transition of the cell cycle upon TCS treatment, leading to a halt in cell cycle progression.…”
mentioning
confidence: 49%
“…important target in cancer therapy (40). G 1 phase arrest by TCS has been previously reported in breast cancer cells (7) and A549 lung cancer cells (41).…”
mentioning
confidence: 92%
“…Several workers reported chromatin condensation and DNA fragmentation of different cancer cells by different mushroom extracts such as EAC extract (10 g/ml) of Cyathus striatus treatment on HPAF-II and PL45 cells 41 , the extract of Agaricus blazei against leukemia NB-4 and K-562 cells 42 , and extract of A. bisporus on CaSki cells after 48 h treatment 38 . Treatment of COLO-205 cells with of three mushrooms (Auricularia polytricha, Macrolepiota procera and Pleurotus ostreatus) revealed the characteristic pattern of DNA laddering on agarose gel electrophoresis 43 . Our DNA laddering assay result is corroborated with other's results.…”
Section: Discussionmentioning
confidence: 99%